The Use of Power Point Presentations to Motivate First Year Secondary School students to learn English THE CASE OF OUED TAGA SECONDARY SCHOOL, BATNA - Maallem, Samia (Journal of Human Sciences, 2019)
This study attempts to show how to  motivate First year secondary school pupils to learn English through the use of one of the ICT’s (Information and Communication Technologies), Power Point Presentations, in the process of teaching and learning English in secondary schools. A pre-test and a post-test are used with a group of 35 students selected randomly. They are taught using power point presentations of some selected items in their units using projectors for a period of 20 weeks. Second, we have utilized two questionnaires, one for EFL teacher in secondary schools and the other for students, in addition to a classroom observation. The obtained results revealed the effectiveness of teaching via PPPs, although some learners prefer the traditional way of learning.